2009
DOI: 10.1111/j.1752-0606.2009.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Children and Psychotropic Medication: A Cautionary Note

Abstract: This report addresses how the mental health field is organized in terms of the use of psychotropic medications with children and adolescents, and the ethical challenge this presents to marriage and family therapists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…[1][2][3][4] However, these criticisms have been primarily based on anecdotal reports, 1-3 studies of small unrepresentative clinical samples, 4 and secondary analyses of large databases on prescription drug use that lack detailed clinical information about individual patients. [5][6][7][8][9] Although there has been a striking increase in prescriptions for psychotropic medications in youth over the past decade, 10,11 there is a lack of empirical data on patterns of medication use among youth with specific mental disorders.…”
Section: Ubstantial Concern Has Beenmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, these criticisms have been primarily based on anecdotal reports, 1-3 studies of small unrepresentative clinical samples, 4 and secondary analyses of large databases on prescription drug use that lack detailed clinical information about individual patients. [5][6][7][8][9] Although there has been a striking increase in prescriptions for psychotropic medications in youth over the past decade, 10,11 there is a lack of empirical data on patterns of medication use among youth with specific mental disorders.…”
Section: Ubstantial Concern Has Beenmentioning
confidence: 99%
“…The results challenge recent concerns over widespread overmedication and misuse of prescribed psychotropic medications in US adolescents. [2][3][4] There was no compelling evidence for either misuse or overuse of psychotropic medications. Only 14.2% of youth with a mental disorder during the past year reported psychotropic use, and the majority who had been prescribed medications, particularly those who received treatment in specialty mental health settings, had a mental disorder with severe consequences and impairment, functional impairment, suicidality, or associated behavioral and developmental difficulties.…”
Section: Commentmentioning
confidence: 99%
“…Although the MGMH assumes the efficacy of psychiatric medication for children, there is growing debate from both within and outside of mainstream psychiatry and pharmacology about the efficacy and safety of many drugs, which have often been found to be at best little more effective than placebo, and at worst harmful (Breggin, , ; Moncrieff, ; Moncrieff and Cohen, ; Timimi, ). In some countries of the global North, ‘mental illness’ in children is framed as an ‘epidemic’, with up to 8 million children in the USA taking one or more psychotropic drugs (Morris and Stone, ), and with prescriptions of psychotropic drugs for children increasing in many countries of the global North and South (Wong and others, ).…”
Section: A Strange Ironymentioning
confidence: 99%
“…Trial evidence has suggested that psychotropic medications are effective in the treatment of youth mental health problems including depressive symptoms, in particular, for younger youth, boys, and youth with less severe depressive symptoms (Strawn, Dobson, & Giles, 2017). However, the use of psychotropic medications among youth has been controversial (Loy, Merry, & Hetrick, 2012; Olfson, Blanco, Liu, Wang, & Correll, 2012) due to concerns of inadequate evidence showing efficacy (Loy et al, 2012; Morris & Stone, 2011; Olfson et al, 2012) and potential risks such as suicidalities (Vries, Jonge, Kalverdijk, & Bos, 2016), weight gain (Loy et al, 2012), and diabetes (Hammerman, Dreiher, & Klang, 2008). Despite such concerns, psychotropic medication use, especially off-label use (usage for symptoms not indicated by authorities such as the U.S. Food and Drug Administration [FDA]), on the clinical youth population has increased dramatically over time (Loy et al, 2012; Olfson et al, 2012; Vries et al, 2016).…”
mentioning
confidence: 99%